الصلابة النفسية وعلاقتها بالسلوك الصحي لدى مرضى السكري - زكري, نرجس; نوار, شهرزاد (جامعة الوادي University of Eloued, 2016)
للدراسة الحالية أهمية جلية تتمثل في أنها تتناول مرضا مزمنا متزايد الانتشار في المجتمع الجزائري يهدد مختلف الفئات العمرية، من خلال تعقد المضاعفات التي يطرحها على المستوى الجسدي والتداعيات التي يفرزها على المستويين النفسي والاجتماعي، بالإضافة إلى التكاليف المادية التي يتطلبها التكفل بالمصابين به، كما تهدف الدراسة إلى الكشف عن العلاقة الارتباطية بين الصلابة النفسية والسلوك الصحي لدى عينة مكونة من 205 فردا من مرضى السكري، اختيروا بطريقة قصدية، وقمنا بصياغة الفرضيات على الشكل التالي: توجد علاقة ارتباطية دالة إحصائيا بين الصلابة النفسية والسلوك الصحي لدى المرضى المصابين بمرض السكري، توجد فروق ذات دلالة إحصائية في الصلابة النفسية والسلوك الصحي لدى مرضى السكري حسب مدة المرض والجنس، وقد اعتمدنا على المنهج الوصفي الارتباطي لتحقيق أهداف الدراسة باستعمال عدة وسائل لجمع البيانات وتحليلها عن طريق الأساليب الإحصائية الملائمة لذلك، وقد توصلت الدراسة إلى وجود علاقة ارتباطية دالة إحصائيا بين الصلابة النفسية والسلوك الصحي لدى المرضى المصابين بمرض السكري وإلى وجود فروق ذات دلالة إحصائية في الصلابة النفسية والسلوك الصحي لدى مرضى السكري حسب مدة المرض، بينما كانت الفروق غير دالة إحصائيا في الصلابة النفسية والسلوك الصحي لدى مرضى السكري حسب الجنس. The current study is clearly important that it deals with a chronic disease increasingly spread in Algerian society which threatens different age groups, through the complexity of the complications posed by the physical level and its implications on the psychological and social levels, in addition to material costs required to care for the patients. The study also aims to detect the correlation between psychological hardiness and health behavior among a sample of 205 individuals from diabetic patients (70 malesand135 females), were chosen in purposive sampling method from the house of diabetes in public hospital Mohamed Boudiaf Ouargla. We have formulated hypotheses considering the duration of the disease and sex as follows: there is a significant correlation between psychological hardiness and health behavior in patients with diabetes; there are statistically significant differences in psychological hardiness and health behavior in patients with diabetes according to the duration of the disease. There are also statistically significant differences in psychological hardiness and health behavior in patients with diabetes according to sex. We used the correlative descriptive approach to achieve the study objectives using several methods of data collection and analysis through appropriate statistical methods to prove or reject the study hypotheses. The study resulted in the presence of statistically significant correlation between psychological hardiness and health behavior in patients with diabetes, and there are statistically significant differences in psychological hardiness and health behavior in patients with diabetes according to the duration of the disease, while there were not statistically significant differences in the psychological hardiness and health behavior in diabetic patients according to sex
دراسة ميدانية بمدينة ورقلة
مقال
Keywords: الصلابة النفسية، السلوك الصحي، مرضى السكري; psychological hardiness, health behavior, diabetic patients.